Mitral isthmus ablation using a circular mapping catheter positioned in the left atrial appendage as a reference for conduction block - Nishiyama, Takahiko (Oncotarget, 2017)
BACKGROUND: For perimitral atrial flutter (PMFL) developing after catheter ablation of atrial fibrillation (AF), to create a complete conduction block at the mitral isthmus (MI) is mandatory to terminate it, however, it is still challenging. METHODS: This study consisted of 80 patients (74 male, 61 ± 8.1 years) undergoing MI ablation. After a circular mapping catheter was positioned at the neck of the left atrial appendage (LAA), the MI ablation was performed on the MI line just below the LAA neck targeting the earliest activation recording site of the LAA catheter during pacing from the coronary sinus (CS). When ablation during CS pacing was not successful, an RF delivery during LAA pacing was applied targeting the earliest activation site just below the MI line. If the endocardial approach failed, an RF application inside the CS was attempted. RESULTS: With the endocardial approach, acute success was achieved in 51/80 patients (64%). Additional epicardial ablation from the CS was performed in 26/29 (90%) endocardially unsuccessful patients and conduction block at the MI was achieved in 21/26 (81%). Overall, complete conduction block at the MI was achieved in 72/80 patients (90%). At a mean follow-up of 16 ± 6 months, 20 patients (25%) had recurrence of atrial arrhythmias (AT: 12, AF: 8), and 10 (AT: 7, AF : 3) underwent a second procedure in which an LMI block line was completed in 3 (33%). PMFL was diagnosed in 6 out of 7 AT patients. No complications were observed. CONCLUSIONS: Creating linear lesions just beneath the neck of the LAA was highly successful under the guidance of a circular mapping catheter in the LAA using a steerable sheath. An RF application from the CS was needed in less than half of the cases.